Disinformation regarding COVID-19 in light of the priorities of the European Commission and the legal regulations binding and currently drafted in Poland - Jaskuła, Lidia Katarzyna (Review of European and Comparative Law, 2022)
Disinformation regarding the COVID-19 pandemic is a global phenomenon. It constitutes a threat to the values protected under the law, health in particular. The primary issue tackled in “Disinformation regarding COVID-19 in the light of priorities of the European Commission and the legal regulations binding and currently drafted in Poland” paper is an attempt at answering the following question: Is eliminating COVID-19 disinformation from public space possible in light of the priorities of the European Commission and the legal regulations already effective and currently being drafted in Poland? The analyses conducted under the paper lead to the conclusions that the provisions currently regulating freedom of expression theoretically constitute a basis for eliminating disinformation from public space but are, in practice, not very effective. This leads to the need for searching for other, more effective legal instruments in this field, both on the level of European Union law making and domestic legislation. Although we may speak of a consensus concerning assessment of the very phenomenon of disinformation the legislative and practical actions taken, both on the domestic level and the European Union level, enable us to indicate substantial and frequently disturbing differences regarding shifting the aspects emphasized by legislation. As compared to the proposed solutions drafted by the European Commission and the drafts of domestic acts, the vastly different approach to the idea of controlling disinformation is clearly visible. Therefore, it must be stated that such circumstances will lead to development of varied legal effects of the drafted regulations that will decide, among other issues, the practical effectiveness or lack thereof in the case of the drafted solutions. In the course of the analysis of the issue constituting the subject of this paper we should concurrently bear in mind that freedom of expression is one of the principles in a democratic state governed by the rule of law.